Xanthomonas wilt of enset in Ethiopia: Geographical spread, impact on production systems and the effect of training on disease management practices - Blomme, Guy; Kearsley, Elizabeth; Buta, Sisay; Chala, Alemayehu; Kebede, Ruhama; Addis, Temesgen; Yemataw, Zerihun (Academic Journals, 2023)
Xanthomonas wilt of enset is a major bacterial disease affecting the entire enset-growing belt in the southern Ethiopian highlands, impacting food security and livelihoods of small-holder subsistence farmers. Through extensive interviews and field validation visits with 354 households covering 19 communities (kebeles), we show 70% of the farms to present current and past enset Xanthomonas wilt infections, with a median of 18% cumulative plant loss across affected years since disease appearance. Training by extension services proved critical for building up farmers’ knowledge on disease management, the effective implementation of disease management, and farmers’ persistence to continue with enset production even when dealing with widespread infestations. After receiving training, farmers were ten times more likely to implement targeted hygienic practices and only half as likely to implement non-recommended cultural practices. Nevertheless, training in disease management did not guarantee consistent implementation by farmers. Farmers remained reluctant to dispose of infected plants, a critical part of Xanthomonas wilt management. Moreover, farmers mostly applied disease management practices once infected plants are observed on the farm, but were unaware of preventive approaches. Extension services had also not reached all communities, with 64% of the households not having received training at the time of the survey.